Xeroderma Pigmentosum Complementation Group C (XPC): Emerging Roles in Non-Dermatologic Malignancies - Nasrallah, Nawar Al; Wiese, Benjamin M.; Sears, Catherine R. (Frontiers in Oncology, 2022)
Xeroderma pigmentosum complementation group C (XPC) is a DNA damage recognition protein essential for initiation of global-genomic nucleotide excision repair (GG-NER). Humans carrying germline mutations in the XPC gene exhibit strong susceptibility to skin cancer due to defective removal via GG-NER of genotoxic, solar UV-induced dipyrimidine photoproducts. However, XPC is increasingly recognized as important for protection against non-dermatologic cancers, not only through its role in GG-NER, but also by participating in other DNA repair pathways, in the DNA damage response and in transcriptional regulation. Additionally, XPC expression levels and polymorphisms likely impact development and may serve as predictive and therapeutic biomarkers in a number of these non-dermatologic cancers. Here we review the existing literature, focusing on the role of XPC in non-dermatologic cancer development, progression, and treatment response, and highlight possible future applications of XPC as a prognostic and therapeutic biomarker.